2020
DOI: 10.1002/ece3.6555
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and maintenance of microbe‐mediated protection under occasional pathogen infection

Abstract: Every host is colonized by a variety of microbes, some of which can protect their hosts from pathogen infection. However, pathogen presence naturally varies over time in nature, such as in the case of seasonal epidemics. We experimentally coevolved populations of Caenorhabditis elegans worm hosts with bacteria possessing protective traits (Enterococcus faecalis), in treatments varying the infection frequency with pathogenic Staphylococcus aureus every host generation, alternating host generations, every fifth … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…This pattern holds during pathogen infection (Figure 1A & 1B) and over a lifetime (Figure 1C-E). The potential of MMP to enhance survival Kloock et al, 2020;Martinez et al, 2016) as well as offspring production (Koehler et al, 2013) has been shown repeatedly. So far, these effects have mainly been considered at the population level.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…This pattern holds during pathogen infection (Figure 1A & 1B) and over a lifetime (Figure 1C-E). The potential of MMP to enhance survival Kloock et al, 2020;Martinez et al, 2016) as well as offspring production (Koehler et al, 2013) has been shown repeatedly. So far, these effects have mainly been considered at the population level.…”
Section: Resultsmentioning
confidence: 96%
“…We used an obligate outcrossing worm population (line EEVD00 from Henrique Teotonio (Theologidis et al, 2014)) where worms carry the fog-2(q71) mutation, preventing hermaphrodites from producing sperm (Theologidis et al, 2014). Worms were kept on Nematode Growth Medium (NGM) (Brenner, 1974), and fed non-pathogenic Salmonella, hereafter referred to as food (Desai et al, 2019;Diaz et al, 2015;Kloock et al, 2020). For pathogenic infection, the Gram positive Staphylococcus aureus strain MSSA476 (Holden et al, 2004) was used.…”
Section: Worm and Bacteria Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…We used an obligate outcrossing worm population [line EEVD00 from Henrique Teotonio (Theologidis et al, 2014)] where worms carry the fog-2(q71) mutation, preventing hermaphrodites from producing sperm (Theologidis et al, 2014). Worms were kept on Nematode Growth Medium (NGM) (Brenner, 1974), and fed with nonpathogenic Salmonella enterica, hereafter referred to as food (Diaz et al, 2015;Desai et al, 2019;Kloock et al, 2020). For pathogenic infection, the Gram-positive Staphylococcus aureus strain MSSA476 (Holden et al, 2004) was used.…”
Section: Worm and Bacteria Systemmentioning
confidence: 99%
“…Defensive mutualisms have been observed across kingdoms [reviewed in ]. The potential of defensive mutualism to enhance survival as well as offspring production has been observed repeatedly (Koehler et al, 2013;King et al, 2016;Kloock et al, 2020). However, most of these examples have only considered population-level effects, while few studies have focused on individual behaviors and/or sex differences between the hosts (McLean et al, 2018).…”
Section: Introductionmentioning
confidence: 99%